(untitled) (Research, Society and Development, 2025)
Iatrogenesis in endodontics represents a significant challenge in daily clinical practice, as it can directly affect the prognosis of treatment and the patient’s overall health. Despite technological advancements in imaging, rotary instrumentation, magnification, and obturation materials, complications arising from operator errors remain frequent. The main iatrogenic incidents in endodontics include perforations of the pulp chamber floor or root walls, instrument fractures, over-instrumentation, overfilling, canal transportation, ledges, blockages, and untreated canals. These complications often stem from a lack of understanding of internal tooth anatomy, inadequate planning, negligence, improper use of technology, or pressure due to limited clinical time. The consequences can range from persistent symptoms to complete treatment failure, necessitating re-intervention or even tooth extraction. This article aims to describe the most common iatrogenic incidents occurring during endodontic treatment, analyze their primary causes and consequences, and present strategies for prevention and management. A qualitative narrative review research was carried out. Emphasis is placed on the importance of proper professional training, the use of evidence-based clinical protocols, the adoption of new diagnostic and treatment technologies, and effective communication with the patient. Preventing iatrogenesis should be a priority in endodontic practice, as it not only ensures better clinical outcomes but also strengthens patient trust in the dental professional, contributing to ethical and safe dental care.